2016
DOI: 10.1371/journal.ppat.1005376
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Hepatitis C Virus Assembly by Distinct Regulatory Regions in Nonstructural Protein 5A

Abstract: Hepatitis C virus (HCV) nonstructural protein (NS)5A is a RNA-binding protein composed of a N-terminal membrane anchor, a structured domain I (DI) and two intrinsically disordered domains (DII and DIII) interacting with viral and cellular proteins. While DI and DII are essential for RNA replication, DIII is required for assembly. How these processes are orchestrated by NS5A is poorly understood. In this study, we identified a highly conserved basic cluster (BC) at the N-terminus of DIII that is critical for pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 77 publications
1
42
0
Order By: Relevance
“…processes; therefore, one would not expect a distinct nucleocapsid-like structure (Zayas et al, 2016). We employed several other approaches, including electron tomography of Jc1 wildtype infected cells, cells treated with brefeldin A to allow accumulation of intracellular viral particles (Gastaminza et al, 2008), and immuno-EM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…processes; therefore, one would not expect a distinct nucleocapsid-like structure (Zayas et al, 2016). We employed several other approaches, including electron tomography of Jc1 wildtype infected cells, cells treated with brefeldin A to allow accumulation of intracellular viral particles (Gastaminza et al, 2008), and immuno-EM.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of virus titers and HCV core protein amounts Virus titers were determined by limiting-dilution assay using Huh7.5 target cells (Blight et al, 2002) and staining of the NS5A protein with the 9E10 monoclonal antibody as described elsewhere (Zayas et al, 2016). Titers of infectious virus are expressed as 50% tissue culture infective dose (TCID 50 ) per mL.…”
Section: Production Of Lentivirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, it has been found that the amphipathic alpha-helix and domains I and II are essential for HCV RNA replication [224,225,230,231]; a recent study showed a critical role for generation of double-membrane vesicles associated with replication [232]. In addition, domain III has a primary role in production of infectious particles with a direct role in coordinating viral assembly [233][234][235].…”
Section: Cyclophilin Inhibitors Against Hcvmentioning
confidence: 99%
“…Hindering trafficking of core or NS5A to LDs either by mutation or by inhibition of critical host factors results in decreased infectious particle production Herker et al, 2010;Liefhebber et al, 2014;Menzel et al, 2012;Miyanari et al, 2007). Vice versa, cells infected with mutant HCV viruses defective in virion morphogenesis often accumulate core at LDs (Gentzsch et al, 2013;Zayas et al, 2016). To investigate whether LD localization of viral proteins is affected by PLIN2 deficiency, we first analyzed levels of core protein in LD fractions from HCV-infected cells.…”
Section: Hcv Protein Trafficking To Lds Is Impaired In Cells Depletedmentioning
confidence: 99%